Survival Analysis of Recovery Rates in Diabetes Mellitus Patients Using the Kaplan-Meier Method (Case Study: Malahayati Islamic Hospital) - Anggreini, Yopie Puspita; Husein, Ismail (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
Diabetes mellitus (DM) is a major global health issue characterized by insulin hormone deficiencies, leading to rising incidence rates and significant risks for society. This study analyzes survival times of DM patients at Malahayati Islamic Hospital Medan using the Kaplan-Meier method for time-to-recovery estimates and the Log-Rank test to evaluate differences in survival functions. Results indicate that survival estimates range from 0.99238 at day 0 to 0.00000 at day 13. No significant differences were found based on gender, age, disease diagnosis, or support type. However, females and older patients showed slightly longer recovery times, and patients with Type II DM recovered faster than those with Pneumonia and Type II DM. Patients receiving Nebulizer and Oxygen support showed quicker recovery compared to those with Thorax Photo, EKG, and Lab support.